MAKING USED CAR SALES WEB APPLICATION USING MACROMEDIA DREAMWEAVER 8.0, PHP AND MYSQL - Heru Setiawan; Munich Heindari Eka Sari, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Rapidly evolving information technology today increasingly easy for every person to obtain information. The Internet is a fast and easy way to convey that information to reach the wider community. Use of website is very useful in trying to  offer and inform the used car sales to consumers. Everything is presented in a web page display that is easily understood by consumers, ranging from the main menu to search for used cars based on the specific physical form, type, and the desired price of the car. Macromedia Dreamweaver 8.0, PHP and MySQL are a few examples of the many software tools that can solve the problem.